A comprehensive review on gout: the epidemiological trends, pathophysiology, clinical presentation, diagnosis and treatment - Kanwal Ashiq; Mayyda Asif Bajwa; Samreen Tanveer; Mehwish Qayyum; Sana Ashiq; Rabia Khokhar; Farah Abid (Journal of the Pakistan Medical Association, 2021)
This review is aimed at provision of an updated knowledge about the gout and highlights the various areas which need to be focused for better healthcare. Relevant published articles in English Language were reviewed by utilizing various available databases including: Google Scholar, Springer Link, Science Direct and MEDLINE. The data reveal a precipitating number of gout cases from the developed countries, while the developing countries on the other hand are faced with an even higher threat. The risk factors and pathophysiology of gout are immaculate and clearly established. Hence, appropriate measures can be explored and worked on to pinpoint diagnosis, effective and economical treatment. Continuous...